Enhancement of cognitive performance in mice and in vitro acetylcholinesterase inhibitory activity of 3,3,4,5,7-pentahydroxyflavone isolated from Cadaba indica - Dhivya, Sundaram; Latha, Subbiah; Selvamani, Palanisamy (Bangladesh Journal of Pharmacology, 2016)
Cadaba indica, a component of traditional siddha medicine, is used for the therapy of gonorrhea, inflammation, eczema etc. The present study shows that it exhibited acetylcholinesterase inhibitory activity (up to 81.5 ± 1.5%) at the concentration of 3 mg/mL, with the IC50 value of 1.8 mg/mL. Furthermore, the ethanol extract of C. indica therapy at a dose of 100 mg/kg p.o significantly ameliorated the cognitive impaired mice in Y-maze task. The active ingredient was identified as 3,3,4,5,7-pentahydroxyflavone. The above results suggest that C. indica would be a potential natural therapeutic remedy for cognitive disorders mediated by cholinergic dysfunction. Video Clip of Methodology: Memory impairment test in mice: 1 min Full Screen Alternative